2018
DOI: 10.1002/celc.201800177
|View full text |Cite
|
Sign up to set email alerts
|

Triphasic Nature of Polymers of Intrinsic Microporosity Induces Storage and Catalysis Effects in Hydrogen and Oxygen Reactivity at Electrode Surfaces

Abstract: Hydrogen oxidation and oxygen reduction are two crucial energy conversion reactions, which are shown to be both strongly affected by the presence of intrinsically microporous polymer coatings on electrodes. Polymers of intrinsic microporosity (PIMs) are known to possess extremely high internal surface area and ability to bind gases under dry conditions. It is shown here that both, hydrogen‐ and oxygen gas binding into PIMs, also occurs under wet or “triphasic” conditions in aqueous electrolyte environments (wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…At a slightly higher potential scan rate ( Figure 7 a) a smaller peak at −0.2 V vs. SCE is observed, but probably not associated with oxygen reduction. The reduction of oxygen at −0.4 V vs. SCE occurs at very negative potential more typical for that of the 2-electron reduction on carbon materials [ 4 ]. This result is striking in that there is very little catalytic ability of the platinum towards oxygen reduction under these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a slightly higher potential scan rate ( Figure 7 a) a smaller peak at −0.2 V vs. SCE is observed, but probably not associated with oxygen reduction. The reduction of oxygen at −0.4 V vs. SCE occurs at very negative potential more typical for that of the 2-electron reduction on carbon materials [ 4 ]. This result is striking in that there is very little catalytic ability of the platinum towards oxygen reduction under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic effects at the nanoscale affect surface reactivity [ 2 ] and can be combined with transport effects that occur in microporous channels and pores in host materials [ 3 ]. Recently, it has been shown that hydrophobic pore structures can lead to triphasic reaction conditions (for example in polymers of intrinsic microporosity or PIMs) and that these can also affect electrocatalyst reactivity [ 4 ]. In electrocatalysis particularly, carbon-based nano-materials are important, as illustrated by recently developed hetero-carbon materials based on nano-dots [ 5 ] and carbon nano-wires or tubes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity for small gaseous species was observed not only for carbonized PIM materials, but also for some materials such as PIM-1. [69] PIM-1 immobilized (in nanoparticulate form) onto a platinum disk electrode and immersed into 10 mM phosphate buffer at pH 7 (see Figure 10A) caused the reduction peak for hydrogen formation to be suppressed, but new anodic peaks for hydrogen oxidation to emerge. These new peaks were explained in terms of molecular hydrogen being bound and stored in PIM-1 directly at the electrode surface.…”
Section: Electrocatalytic Processes Enhanced By Pim Membranesmentioning
confidence: 99%
“…Also, hydrogen evolved in the presence of PIM-7 is "trapped" and re-oxidised (see the broad peak in Figure 5D) consistent with recent observations of hydrogen storage in PIM-1 materials. [17] The onset of hydrogen evolution is linked to the position of the reduction peak (formation of PdH x ) and both processes are likely to be coupled. Therefore, the shift in the peak to more positive potential and the enhanced rate in hydrogen evolution caused by PIM-7 should depend on a similar mechanism.…”
Section: Pim-7 Modified Glassy Carbon Iii: Palladium Electrodepositimentioning
confidence: 99%
“…[15,16] The polymer of intrinsic microporosity PIM-1 (see molecular structure in Figure 1) has recently been shown to bind gases such as molecular hydrogen or oxygen at the electrode surface under "triphasic" conditions (with coexisting solid, liquid, and gaseous phases), thereby affecting electrocatalytic reactions. [17] It is of interest to further explore effects of similar PIM coatings on catalytic surfaces.…”
Section: Introductionmentioning
confidence: 99%